Analisa Dan Evaluasi Sistem Transportasi Publik Bus Rapid Transit (Brt) Trans Semarang Koridor Iv Kota Semarang - Widodo, Agus; Yudho Putranto, Ardi; Handajani, Mudjiastuti; Muldiyanto, Agus (Jurnal Civil Engineering Study, 2023)
Population growth has made transportation in Indonesia, especially in the city of Semarang, also growing, one of the public transportation currently being developed in the city of Semarang is the BRT. Of the 7 operating corridors, BRT corridor IV (four) encountered many obstacles and problems, including the small number of bus passengers so that the revenue from the fares that were collected did not cover operational costs. This study aims to find out about the existing service standards for BRT in Corridor IV Semarang; Analyzing the performance and service of BRT buses in Corridor IV Semarang based on the number of passengers, travel speed, load factor, headway, and number of fleets; and Know the things that need to be fixed on this transportation. The method we use is field observation and secondary data analysis. The results showed that BRT Trans Semarang Corridor IV has 20 fleets with details of 18 operating fleets and 2 fleets for backup. The load factor value is 53% which meets the existing standards, the BRT Trans Semarang Corridor IV headway value is 13.51 minutes which is not in accordance with the existing regulatory requirements. The average speed is 14.68 km/hour which is below the maximum regulation limit and the distance covered is 237.04 km which is not accordance with the standard travel distance.